2021
DOI: 10.3390/ijms22136876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nucleophile’s Nature on Chloroacetanilide Herbicides Cleavage Reaction Mechanism. A DFT Study

Abstract: In this study, the degradation mechanism of chloroacetanilide herbicides in the presence of four different nucleophiles, namely: Br−, I−, HS−, and S2O3−2, was theoretically evaluated using the dispersion-corrected hybrid functional wB97XD and the DGDZVP as a basis set. The comparison of computed activation energies with experimental data shows an excellent correlation (R2 = 0.98 for alachlor and 0.97 for propachlor). The results suggest that the best nucleophiles are those where a sulfur atom performs the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…A possible explanation is that the larger and longer alkoxyalkyl has a smaller electrophilic constant. 23,41 A previous study indicated that S 2− (as a nucleophile) could bind to CAAHs. 15 Thus, the smaller the electrophilic constant, the stronger its bond to the nucleophile, thus lowering the degradation efficiency.…”
Section: Degradation Kinetics and Substrate Spectra Of Strain Srb-5mentioning
confidence: 99%
“…A possible explanation is that the larger and longer alkoxyalkyl has a smaller electrophilic constant. 23,41 A previous study indicated that S 2− (as a nucleophile) could bind to CAAHs. 15 Thus, the smaller the electrophilic constant, the stronger its bond to the nucleophile, thus lowering the degradation efficiency.…”
Section: Degradation Kinetics and Substrate Spectra Of Strain Srb-5mentioning
confidence: 99%
“…DFT calculations have been proven effective in the study of reaction mechanisms. For instance, the reaction mechanism of bi-ATDO fast amide cleavage through an intramolecular nitrogen nucleophilic attack was elucidated [12], as was the effect of the nucleophilic nature in the degradation mechanism of chloroacetanilide herbicides [29]. Proton transfer between amide dimers has also been studied to better understand biological enzymatic systems [30].…”
Section: Introductionmentioning
confidence: 99%